Penyediaan Rekam Medis Guna Mendukung Standar Akreditasi MIRM 13 Di RSUD Panembahan Senopati Bantul - Kori Puspita Ningsih; Endang Purwanti; Rahayu Iskandar (Indonesian of Health Information Management Journal (INOHIM), 2022)
AbstractThe accreditation standard for Medical Record Information Management (MIRM) 13 regulates the provision of medical records. The regulation aims to ensure the continuity of patient health documentation. This study describes the condition of medical records starting from numbering, ordering, and making and retrieving medical records to support patient care documentation according to hospital accreditation standards in the MIRM chapter 13. This type of research is descriptive with a retrospective approach. The results showed that Panembahan Senopati Hospital Bantul already has Medical Record Service Guidelines and Standard Operating Procedures regulations. The regulation provides medical records for numbering, ordering, and creating and retrieving medical records to support patient service documentation. Panembahan Senopati Hospital Bantul implements an automated unit numbering system with the support of an RS SIM. They set the medical order after the patient goes home, both outpatient and inpatient. Making and retrieving medical records is part of implementing the unit numbering system. New patients make medical records when served at the registration section, while medical records take from the filing section for old patients. If medical records were not ready at the return visit, the professional HIM used a follow-up outpatient medical record form and combined it after the medical records were prepared. The regulation and the medical supply system show that Panembahan Senopai Hospital, Bantul, has implemented the MIRM standard 13 ep 1-5. However, implementation constraints are still on the MIRM 13 ep 4.Keywords: provision, numbering, assembling, retrieval, medical recordsAbstrakDalam standar akreditasi Manajemen Informasi Rekam Medis (MIRM) 13 mengatur penyediaan rekam medis. Rerulasi tersebut bertujuan menjamin kesinambungan dokumentasi kesehatan pasien. Penelitian ini bertujuan untuk menggambarkan penyediaan rekam medis mulai dari penomoran, urutan rekam medis, pembuatan dan retrieval rekam medis guna mendukung dokumentasi pelayanan pasien sesuai standar akreditasi rumah sakit pada bab MIRM 13. Jenis penelitian dekriptif dengan pendekatan retrospektif. Hasil penelitian menunjukkan bahwa RSUD Panembahan Senopati Bantul sudah memiliki regulasi berupa Pedoman Pelayanan Rekam Medis dan Standar Prosedur Operasional yang mengatur penyediaan rekam medis untuk penomoran, urutan rekam medis, pembuatan dan retrieval rekam medis guna mendukung dokumentasi pelayanan pasien. RSUD Panembahan Senopati Bantul menerapkan sistem penomoran unit yang sudah terotomatisasi dengan dukungan SIM RS. Pengaturan urutan rekam medis dilakukan setelah pasien pulang baik rawat jalan maupun rawat inap. Pembuatan dan retrieval rekam medis merupakan bagian dari implementasi sistem penomoran unit. Pasien baru dibuatkan rekam medis saat di layani di bagian pendaftaran, sedangkan untuk pasien lama diambilkan rekam medis dari bagian filing. Apabila rekam medis tidak ditemukan pada saat kunjungan ulang maka petugas menggunakan formulir rekam medis rawat jalan lanjutan dan formulir tersebut akan digabungkan setelah rekam medis ditemukan. Adanya regulasi dan sistem penyediaan rekam medis tersebut menunjukkan RSUD Panembahan Senopai Bantul telah mengimplemantasikan standar MIRM 13 ep 1-5. Namun masih terdapat kendala implementasi pada standar MIRM 13 ep 4.Kata kunci: penyediaan, penomoran, urutan, retrieval, rekam medis